Bringing time back to childhood. Slowness and art as educational elements after the period of social distancing: Slowness and art as educational elements after the period of social distance. - Sánchez Serrano, Silvia; Muratori, Marilena (Journal of Learning Styles, 2022)
In a constantly evolving society where acceleration and immediacy predominate, people have been forced into a strong change. The health crisis provoked by Covid-19, has forced us to take the time awareness as a highly complex element, highlighting the value of cognition of its three dimensions (past-present-future). The purpose of this essay is to rebuild the sense of time, understood as a one of the key elements of life in society and in the educational processes. Rediscovering the waiting, the slowness is essential for current education. In this sense, it is necessary to educate in order to give back to childhood the possibility of living the present, like the only way to think about the past. The aim of this paper is to justify, thought a bibliographic review, the need to rethink the concept of time understood as an indispensable dimension for the development of the individual and for the construction of community after a time of social distancing. For that, the essay is based on the importance of using the arts in the education to recover a balanced temporary, as well as strengthen the individual and his social relations within the community linking three elements: education, art and time.